ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH DI KELURAHAN KOYA, KECAMATAN TONDANO SELATAN - Alvio G. Onibala; Mex L. Sondakh; Rine ., Kaunang; Juliana ., Mandei (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the influence of the use of production factors on rice farming production. This research was conducted in Urban Village of Koya, Sub-district of South Tondano, Minahasa District by using primary data and secondary data. Sampling in this research was done by using Simple Random Sampling method with 60 farmers as respondents. The variables measured in this research are production, land area, amount of labor, amount of phonska fertilizer, amount of urea fertilizer, number of seeds and amount of pesticide. The data analysis used is Cobb Douglas model regression analysis to see the influence of each factor of production on the produced production. Simultaneously variable of land area, seed, urea fertilizer, phonska fertilizer, pesticide and labor have an effect on rice field production in Koya. Individual variables of land area, urea seed and fertilizer have a significant effect on rice production.